Functionalized carbon nanotube reinforced polymer nanocomposite microcapsules with enhanced stiffness - Jagtap, Siddheshwar B.; Patil, Vishal D.; Suresh, Karthika; Ram, Farsa; Mohan, Muthu Subramanian; Rajput, Shatruhan S.; Patil, Shivprasad; Shukla, Parshuram G.; Shanmuganathan, Kadhiravan (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Microcapsules with tunable mechanical properties are highly desirable in pressure sensitive applications. We report here a facile approach to prepare polyurea/multiwall carbon nanotube (MWCNTs) nanocomposite microcapsules (MICs) with enhanced stiffness. A model compound dimethyl phthalate (DMP) was used as core material. MWCNTs were modified with reactive functional groups namely carboxyl (-COOH), amines (-NH2), and isocyanates (-NCO) to ensure a stronger interface between polymer wall and MWCNTs. Functionalization of MWCNTs was corroborated by Fourier transformed infrared spectroscopy (FTIR). Scanning electron microscopy (SEM) was employed to study the surface morphology of MICs. The presence of MWCNTs in the microcapsule wall was confirmed by transmission electron microscopy (TEM). MICs with functionalized MWCNTs show almost 100% increase in stiffness with respect to pristine capsules. All MICs show 92-97 +/- 1% encapsulation efficiency. The approach used in this paper can be broadly utilized to tune the mechanical properties of the microcapsules.